THE MINERAL OXIDE CONTENTS OF THE TEGAL LENGA BEACH IRON SAND - Suardana, Putu; Manuaba, I B. Sujana; Wendri, Nyoman (BULETIN FISIKA; Vol 20 No 2 (2019): BULETIN FISIKA, 2019)
Iron sand samples were taken from the top layer of the Tegal Lenga beach sand. It was purified by the Magnetic Separation method, it was found that the average weight fraction of the Tegal Lenga beach iron sand is 54.71%. With X-ray flouresence (XRF) characterization obtined that the minerals oxide contained in the iron sand of the Tegal Lenga beach are magnesium diiron (III) oxide (MgFe 2 O 4 ), silicare alumina calcium alumina alumina (Ca (Mg 0.5 Al 0 . 5 ) (Al 0 . 5 Si 1 . 5 O 6 )), and iron iron (III) titanium aluminum magnesium vanadium manganese silicon oxide (Fe 4 . 42 Fe 5 . 245 Ti 4.72 Al 0 . 7 Mg 0.4 Cr 0.3 V 0.15 Fe 7.82 Mn 0 . 114 Si 0.05 O 6 ) with the volume fraction of each compound are 62.95%, 39.78%, and 39.74%